Extracellular miRNA: a collision of two paradigms - Turchinovich, Andrey; Tonevitsky, Alexander; Burwinkel, Barbara (Trends in biochemical sciences, 2016)
Since their discovery in 2008, extracellular miRNAs (ex-miRNAs) have persisted as one of the major themes of molecular and cellular biology. The main reason for this remarkable interest is the increasing number of research papers reporting that cell-free circulating miRNA mediates both short-range and distant communication between various cells, and could impact on diverse physiological and pathological processes. However, there are also multiple conflicting lines of evidence that challenge the biological significance of circulating ex-miRNA, suggesting that they are merely byproducts of cell activity and cell death without any particular function. This review aims to summarize these contrasting opinions and to foster further experimental validation of both paradigms.